Applications of Bacterial Cellulose as a Natural Polymer in Tissue Engineering. Issue 7 (11th March 2021) - Bouhlouli, Mahboubeh; Pourhadi, Masoumeh; Karami, Farshid; Talebi, Zahra; Ranjbari, Javad; Khojasteh, Arash
Abstract : Choosing the material with the best regeneration potential and properties closest to that of the extracellular matrix is one of the main challenges in tissue engineering and regenerative medicine. Natural polymers, such as collagen, elastin, and cellulose, are widely used for this purpose in tissue engineering. Cellulose derived from bacteria has excellent mechanical properties, high hydrophilicity, crystallinity, and a high degree of polymerization and, therefore, can be used as scaffold/membrane for tissue engineering. In the current study, we reviewed the latest trends in the application of bacterial cellulose (BC) polymers as a scaffold in different types of tissue, including bone, vascular, skin, and cartilage. Also, we mentioned the biological and mechanical advantages and disadvantages of BC polymers. Given the data presented in this study, BC polymer could be suggested as a favorable natural polymer in the design of tissue scaffolds. Implementing novel composites that combine this polymer with other materials through modern or rapid prototyping methods can open up a great prospect in the future of tissue engineering and regenerative medicine.